1915 Kan. Sess. Laws 347 - (:unkn) unknown (My University, 1915)
An Act providing for Public Safety by Regulating the Storage Handling and Disposition of Dynamite, Giant Powder, Nitro-glycerine, Gun Cotton and Other Detonating Explosives, Providing Penalties for Violation of this Act and Repealing all Acts in Conflict Herewith, § 1: Any person, firm or corporation, in this state, who shall sell, give away or otherwise dispose of, any dynamite, giant powder, nitro-glycerine, gun cotton or other detonating explosive, shall keep a record, in a substantially bound book, which record shall set forth the kind and amount of explosives delivered, the time of delivery, the uses and purposes for which same are delivered and the place at which it is to be used
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER